Interpreting Herodotus - Irwin, Elizabeth; Harrison, Thomas (Oxford University Press, 2018)
Developing the themes and ideas of Charles W. Fornara's seminal publication Herodotus: An Interpretative Essay (Oxford, 1971), this volume offers a new look at the Histories in light of the explosion of scholarship in the intervening years, focusing particularly on how we can interpret Herodotus' work in terms of the context in which he wrote
Includes bibliographical references and indexes
Keywords: Fornara, Charles W -- Herodotus; Herodotus; Herodotus -- Criticism and interpretation; Konferenzschrift -- 2013 -- New York